2017
DOI: 10.4172/2471-2663.1000133
|View full text |Cite
|
Sign up to set email alerts
|

Osteocalcin: A New Biomarker for Non Alcoholic Fatty Liver Disease (NAFLD) in Children and Adolescents

Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) is a common liver disease in adults but uncommon in Pediatrics. Patients with chronic liver disease are at increasing risk of developing metabolic bone disease which may be attributed to decreased Osteocalcin which is involved in bone extracellular matrix mineralization. Aim of the work: was to measure serum osteocalcin levels in children and adolescents with NAFLD and to investigate the relationship with variables degrees of NAFLD. Materials and methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Patients with NAFLD exhibited lower serum osteocalcin levels than those in the control group and the osteocalcin concentration were inversely correlated with liver enzymes and the severity of NAFLD. In addition, a serum osteocalcin level below 44.5 ng/ml was revealed to be a good predictor of hepatic steatosis severity with a sensitivity and specificity of 80% (57,58). Furthermore, normoglycemic postmenopausal women with NAFLD exhibited significantly lower serum osteocalcin levels than controls and the serum osteocalcin levels exhibited a negative correlation with the fatty liver index values, even following adjusting for confounding factors (51).…”
Section: Importance Of Biological Experimental Findings Regarding Ostmentioning
confidence: 96%
“…Patients with NAFLD exhibited lower serum osteocalcin levels than those in the control group and the osteocalcin concentration were inversely correlated with liver enzymes and the severity of NAFLD. In addition, a serum osteocalcin level below 44.5 ng/ml was revealed to be a good predictor of hepatic steatosis severity with a sensitivity and specificity of 80% (57,58). Furthermore, normoglycemic postmenopausal women with NAFLD exhibited significantly lower serum osteocalcin levels than controls and the serum osteocalcin levels exhibited a negative correlation with the fatty liver index values, even following adjusting for confounding factors (51).…”
Section: Importance Of Biological Experimental Findings Regarding Ostmentioning
confidence: 96%
“…Te GH/ IGF-1 axis is involved in skeletal muscle protein metabolism, bone growth, and remodeling [2,47]. In addition, bone fat and energy metabolism are associated with serum osteocalcin which is a good predictor of the severity of hepatic steatosis with a sensitivity and specifcity of 80% when its level is less than 44.5 ng/mL [48,49]. Terefore, the serum screening of BTMs is a key strategy and possible theoretical basis for detecting osteoporosis in the NAFLD population.…”
Section: Discussionmentioning
confidence: 99%
“…Osteocalcin improves NAFLD's progression by stimulating the Nrf2 pathway to cause oxidative stress and inhibits the JUK pathway, where low levels of osteocalcin are observed in children with NAFLD and who suffer from obesity, this decrease also increases with disease severity, osteocalcin plays a key role in the metabolism of fats and glucose, thus contributing to promoting disease progression [15]. Low levels of osteocalcin in children and adolescents with NAFLD are a vital sign of disease severity for this age group [16]. Osteocalcin regulates bone metabolism and is a diagnostic criterion for bone formation in the body, the previous studies indicated the relationship of NAFLD with the percentage of minerals in bones where there is an inverse relationship between them in men, in particular the density of minerals present in the hips [17].…”
Section: Discussionmentioning
confidence: 99%